2018
DOI: 10.2106/jbjs.rvw.17.00159
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Clinically Important Difference: Current Trends in the Orthopaedic Literature, Part I: Upper Extremity

Abstract: The MCID is increasingly used as a measure of patients' improvement. However, the MCID does not yet adequately capture the clinical importance of patients' improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 93 publications
4
77
0
Order By: Relevance
“…Our results are consistent with previous studies 23–25. A previous review of MIDs of upper extremity instruments that appeared in selected orthopaedic journals from 2014 to 2016 found a wide range of MIDs for the Constant score (8–36) and reported a pain VAS MID of 1.4 on 10-point scale 26. Reviews of pain VAS MIDs in shoulder injuries found a range of 0.5–3.0 24 36 46 47.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with previous studies 23–25. A previous review of MIDs of upper extremity instruments that appeared in selected orthopaedic journals from 2014 to 2016 found a wide range of MIDs for the Constant score (8–36) and reported a pain VAS MID of 1.4 on 10-point scale 26. Reviews of pain VAS MIDs in shoulder injuries found a range of 0.5–3.0 24 36 46 47.…”
Section: Discussionsupporting
confidence: 92%
“…13,15,36 However, as recent literature has emphasized, it is critical to use the MCID to judge the effectiveness of the treatment as perceived by the patients instead of just the P value to interpret the results. 8,18,21,25,38 Only 1 study has compared the improvement in postoperative function based on the MCID of the Flexilevel Scale of Shoulder Function (FLEX-SF) score and found it to be clinically significantly worse in the rRCR group than in the pRCR group. 15 In contrast, the patients in our study who had revision and primary surgery experienced similar pain relief and function in terms of clinically meaningful difference at the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used MCID along with the statistical significance to compare the results between study groups, which is aligned with the recent emphasis on reporting the clinical significance of the observed difference in clinical outcomes. 8,18,21,25,38…”
Section: Discussionmentioning
confidence: 99%
“…2 To date, clinically significant outcome scores have not been established for PMR, which would serve as anchor points for predicted improvement after surgery. 6 Analysis of specific sports outcomes and weight-lifting outcomes offers a more comprehensive picture of expected postoperative outcome for this patient cohort, which has not been provided before in the literature.…”
Section: Discussionmentioning
confidence: 99%